DEVELOPMENT OF STUDENT DISCIPLINE CHARACTER EDUCATION THROUGH CEREMONY ACTIVITIES AT BUMIREJO STATE ELEMENTARY SCHOOL - Retnoningsih, Wahyu; Khasanah, Wahyu; Chamdani, Muhamad (Universitas Sebelas Maret, 2018)
The purpose of this study was 1) to know the concept of conducting ceremonial activities in Bumirejo State Elementary School 5 and 2) to describe the ceremonial activities in developing the discipline character of students. The method used in this study is descriptive-qualitative method with interviews, observation, and documentation that aims to get a general understanding of social conditions from the perspective of participants (Rahmat, 2009). The results of this study are 1) the concept of conducting ceremonial activities in Bumirejo State Elementary School 5 and 2) can describe the ceremonial activities in developing the discipline character of students. So, the conclusion of this study is that the ceremonial activities can develop the discipline character of students in Bumirejo State Elementary School 5.